HUBUNGAN PENGETAHUAN DENGAN PERILAKU SADARI (PERIKSA PAYUDARA SENDIRI ) SEBAGAI TINDAKAN DETEKSI DINI KANKER PAYUDARA PADA SISWI KELAS X DI SMA NEGERI 3 KOTA PADANGSIDIMPUAN - Nurhanifah Siregar (Jurnal Maternitas Kebidanan, 2021)
ABSTRACT Breast cancer is a type of malignant tumor that is still the number one killer. Indonesia at first breast cancer attacks women aged over 30 years, but now the age of breast cancer patients becomes young or teenagers. Breast cancer can be found as early as BSE. If you don't do BSE breast cancer will be detected at an advanced stage and ultimately cause death. Early detection can reduce mortality by 25-30%. Breast self-examination is very important to be recommended for the community or adolescents because almost 86% of lumps in the breast are found by patients themselves.This type of research is an analytical survey with cross sectional design, a sample of 45 people. The measuring instrument is a questionnaire with 22 questions developed by researchers. This study aims to determine the relationship between independent and dependent variables. The analysis used is univariate analysis to see the description of the characteristics of respondents and bivariate tests using Chisquare.The results showed that there was no relationship between knowledge and conscious behavior (P-value = 0.487, where P-value was 5 0.05). It was emphasized with the results of the study, there were 34 students with only 1 knowledgeable behavior. With that, good student knowledge will not necessarily understand good BSE behavior. It could be less knowledgeable but understand good BSE behavior.Based on the results of this study, suggestions for students to care more about their health, more often to check their own breasts after each menstrual period - 7 to 10 days from the first day of menstruation, reduce the habits of fast food patterns because it will accelerate the trigger of breast cancer. Keywords: BSE Behavior, Early Detection of Breast Cancer